Numerical Simulation of Heavy and Light Pollutants Motion as a Tool of Experimental Data Verification - Ondrej Zavila; Lenka Herecova; Dalibor Micek; Tomas Hejzlar (Communications - Scientific letters of the University of Zilina, 2011)
Computational Fluid Dynamics (CFD) codes including software ANSYS Fluent represent worldwide accomplished group of tools for fluid mechanics phenomena numerical simulations. These codes are based on numerical solution of partial differential equations that are not to be solved analytically. The only way of numerical data verification is to execute comparison with experimental data respecting the same boundary conditions. This article deals with experimental data verification by using CFD code ANSYS Fluent 12.1.4 as a tool for numerical simulations. Comparison of pollutant’s plume and its scattering considering different density of each pollutant is the main point of the problem. Results are presented by means of commented graphs and pictures.